An X-ray absorption and photoemission study of the electronic structure of Ni porphyrins and Ni N-confused porphyrin - SENGE, MATHIAS; SERGEEVA, NATALIA (My University, 2008)
Investigations of chemical bonding and electronic structure features for polycrystalline (porphyrinato)nickel (II) (NiP, the simplest Ni porphyrin), (5,10,15,20-tetraphenylporphyrinato)nickel (II) (NiTPP) and (2-aza-21-carba-5,10,15,20-tetraphenylporphyrinato)nickel (II) (N-confused NiTPP, NiNCTPP) have been performed by means of high-resolution soft x-ray absorption and x-ray photoemission spectroscopy. The Ni 2p3/2 x-ray absorption spectra show strong ?-back-bonding in these compounds leading to a high-energy shift (1.2 eV for the NiP and NiTPP) of the entire absorption structure compared to Ni metal. It has been found that the main absorption line of the Ni 2p3/2 spectrum of the NiNCTPP is shifted by an additional 0.5 eV to higher energies in comparison with those for other nickel porphyrins. This shift is evidence of stronger back-donation (metal-to-ligand charge transfer) and a smaller effective number of 3d electrons on the central Ni atom in the NiNCTPP as compared to other Ni porphyrins. The confused N atom in the NiNCTPP is of pyrrolic type (protonated nitrogen), which was confirmed by the N 1s absorption and core-level photoemission spectra.
PUBLISHED
Keywords: Chemistry; 3d transition metal; Nanoscience & Materials